THE EVOLUTION AND IMPACT OF AI/ML CHATBOTS IN ENTERPRISE APPLICATIONS: A TECHNICAL ANALYSIS - Manpreet Singh Sachdeva (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This technical article examines the implementation and evolution of AI/ML-powered chatbots in enterprise telecommunications environments, focusing on deployments at Vodafone and Verizon. Through detailed analysis of system architectures, performance metrics, and business outcomes, we demonstrate how advanced NLP models and machine learning algorithms have transformed customer service operations and incident management. The article reveals significant improvements, including a 42% reduction in customer interaction costs, 78% first-contact resolution rate, and 99.99% system uptime. Vodafone's Tobi virtual assistant, processing 2.5 million monthly interactions, achieved a cost reduction of 67% per interaction (€0.15 versus industry standard €0.45) while maintaining a CSAT score of 4.2 out of 5. Verizon's incident management system demonstrated a 35% reduction in Mean Time to Resolution and 78.7% decrease in false alerts, with classification accuracy improving from 65% to 87%. The article also highlights technological advancements in multi-language support across 12 major languages with 95.8% translation accuracy, predictive maintenance capabilities reducing downtime by 55%, and automated incident resolution. Future developments include GPT-4 integration with enhanced context handling up to 64K tokens, AR/VR technical support integration promising 40% faster issue resolution, and advanced predictive network maintenance systems projected to save €2.8M annually. These implementations establish new benchmarks for enterprise AI systems while providing a framework for future telecommunications service delivery enhancement.